2016
DOI: 10.1111/nhs.12302
|View full text |Cite
|
Sign up to set email alerts
|

Resident and family member perceptions of cultural diversity in aged care homes

Abstract: Similar to many developed nations, older people living in residential aged care homes in Australia and the staff who care for them have become increasingly multicultural. This cultural diversity adds challenges for residents in adapting to the care home. This study explores: (i) residents' and family members' perceptions about staff and cultural diversity, and (ii) culturally and linguistically diverse residents' and family members' experiences. An interpretive study design employing a thematic analysis was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The aim of this study was to examine active actions (agencies) residents and staff undertook in their daily interactions to improve CCC and the social conditions (structures) that might enable and sustain these actions. This study reports in part on a larger critical action research project entitled ‘Developing the multicultural workforce to improve the quality of care for residents’ that is reported elsewhere (Xiao et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to examine active actions (agencies) residents and staff undertook in their daily interactions to improve CCC and the social conditions (structures) that might enable and sustain these actions. This study reports in part on a larger critical action research project entitled ‘Developing the multicultural workforce to improve the quality of care for residents’ that is reported elsewhere (Xiao et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Often family members are informal care partners to their relative living with dementia prior to transitioning into LTC, which may play a part in their continued level of involvement after their relative has moved into a care home (Graneheim et al, 2014). Eating together is a familiar ritual among most families prior to moving into LTC, thus, mealtimes may be able to provide a medium through which families of all structures and diverse ethno‐cultural backgrounds can exercise their cultural traditions and norms with their relatives, both as a way of providing dedicated, individualized care to the resident and to reinforce familial bonds (Henkusens et al, 2014; Petersen et al, 2014; Xiao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 12 ] investigated the best practice of providing person-centred care for residents with moderate to advanced dementia from diverse ethnic backgrounds and showed that it was associated with residents’ perceptions of their individual preferences and feelings of belonging. Further, other previous research focusing on residents’ and family members’ perceptions of cultural diversity in aged care homes [ 13 ] found that they were generally satisfied with the cultural and linguistic diversity in care homes.…”
Section: Introductionmentioning
confidence: 90%